Perkembangan Jaringan Kerjasama Perpustakaan dan Informasi - Sri Rahayu; Putri Septiani; Yusniah Yusniah; Feny Arsella; Doni Sabdan Tanjung (Da'watuna: Journal of Communication and Islamic Broadcasting, 2022)
In the current era of openness, the presentation of data and information is very important to convey the widest possible information to the public. Due to the diversity of information needs, limited information resources and changing behavior of information users, no information organization can meet all user needs. To meet user needs and provide optimal service to users, there must be cooperation and networks between information institutions. One of these information institutions is the library, which will be the subject of this article. This article will discuss developments, forms of cooperation, development situations and inhibiting factors of library and information cooperation networks. The data collection method uses library research, both printed and online. The results of this study are to provide data and information on the development of library collaboration networks, as well as information that can be used to provide input to libraries and other information media in collaboration. Keywords: library cooperation, library network development, information.